Drawbacks in the use of unconventional hydrophobic anhydrides for histone derivatization in bottom‐up proteomics PTM analysis. Issue 9 (May 2015) - Sidoli, Simone; Yuan, Zuo‐Fei; Lin, Shu; Karch, Kelly; Wang, Xiaoshi; Bhanu, Natarajan; Arnaudo, Anna M.; Britton, Laura‐Mae; Cao, Xing‐Jun; Gonzales‐Cope, Michelle; Han, Yumiao; Liu, Shichong; et al.
Abstract : MS‐based proteomics has become the most utilized tool to characterize histone PTMs. Since histones are highly enriched in lysine and arginine residues, lysine derivatization has been developed to prevent the generation of short peptides (<6 residues) during trypsin digestion. One of the most adopted protocols applies propionic anhydride for derivatization. However, the propionyl group is not sufficiently hydrophobic to fully retain the shortest histone peptides in RP LC, and such procedure also hampers the discovery of natural propionylation events. In this work we tested 12 commercially available anhydrides, selected based on their safety and hydrophobicity. Performance was evaluated in terms of yield of the reaction, MS/MS fragmentation efficiency, and drift in retention time using the following samples: (i) a synthetic unmodified histone H3 tail, (ii) synthetic modified histone peptides, and (iii) a histone extract from cell lysate. Results highlighted that seven of the selected anhydrides increased peptide retention time as compared to propionic, and several anhydrides such as benzoic and valeric led to high MS/MS spectra quality. However, propionic anhydride derivatization still resulted, in our opinion, as the best protocol to achieve high MS sensitivity and even ionization efficiency among the analyzed peptides.